Genome-wide characterization of SOS1 gene family in potato (Solanum tuberosum) and expression analyses under salt and hormone stress - Liang, Liqin; Guo, Liuyan; Zhai, Yifan; Hou, Zhiling; Wu, Wenjing; Zhang, Xinyue; Wu, Yue; Liu, Xiaona; Guo, Shan; Gao, Gang; Liu, Weizhong (Frontiers in Plant Science, 2023)
Salt Overly Sensitive 1 (SOS1) is one of the members of the Salt Overly Sensitive (SOS) signaling pathway and plays critical salt tolerance determinant in plants, while the characterization of the SOS1 family in potato (Solanum tuberosum) is lacking. In this study, 37 StSOS1s were identified and found to be unevenly distributed across 10 chromosomes, with most of them located on the plasma membrane. Promoter analysis revealed that the majority of these StSOS1 genes contain abundant cis-elements involved in various abiotic stress responses. Tissue specific expression showed that 21 of the 37 StSOS1s were widely expressed in various tissues or organs of the potato. Molecular interaction network analysis suggests that 25 StSOS1s may interact with other proteins involved in potassium ion transmembrane transport, response to salt stress, and cellular processes. In addition, collinearity analysis showed that 17, 8, 1 and 5 of orthologous StSOS1 genes were paired with those in tomato, pepper, tobacco, and Arabidopsis, respectively. Furthermore, RT-qPCR results revealed that the expression of StSOS1s were significant modulated by various abiotic stresses, in particular salt and abscisic acid stress. Furthermore, subcellular localization in Nicotiana benthamiana suggested that StSOS1-13 was located on the plasma membrane. These results extend the comprehensive overview of the StSOS1 gene family and set the stage for further analysis of the function of genes in SOS and hormone signaling pathways.